Migration trajectories of the diamondback moth Plutella xylostella in China inferred from population genomic variation. Issue 4 (29th November 2020) - Chen, Ming‐Zhu; Cao, Li‐Jun; Li, Bing‐Yan; Chen, Jin‐Cui; Gong, Ya‐Jun; Yang, Qiong; Schmidt, Thomas L; Yue, Lei; Zhu, Jia‐Ying; Li, Hu; Chen, Xue‐Xin; Hoffmann, Ary Anthony; et al.
Abstract: BACKGROUND: The diamondback moth (DBM), Plutella xylostella (Lepidoptera: Plutellidae), is a notorious pest of cruciferous plants. In temperate areas, annual populations of DBM originate from adult migrants. However, the source populations and migration trajectories of immigrants remain unclear. Here, we investigated migration trajectories of DBM in China using genome‐wide single nucleotide polymorphisms (SNPs) genotyped using double‐digest RAD (ddRAD) sequencing. We first analyzed patterns of spatial and temporal genetic structure among southern source and northern recipient populations, then inferred migration trajectories into northern regions using discriminant analysis of principal components (DAPC), assignment tests, and spatial kinship patterns. RESULTS: Temporal genetic differentiation among populations was low, indicating that sources of recipient populations and migration trajectories are stable. Spatial genetic structure indicated three genetic clusters in the southern source populations. Assignment tests linked northern populations to the Sichuan cluster, and central–eastern populations to the southern and Yunnan clusters, indicating that Sichuan populations are sources of northern immigrants and southern and Yunnan populations are sources of central–eastern populations. First‐order (full‐sib) and second‐order (half‐sib) kin pairs were always found within populations, but ~ 35–40% of third‐order (cousin) pairs were found in different populations. Closely related individuals in different populations were found at distances of 900–1500 km in ~ 35–40% of cases, while some were separated by > 2000 km. CONCLUSION: This study unravels seasonal migration patterns in the DBM. We demonstrate how careful sampling and population genomic analyses can be combined to help understand cryptic migration patterns in insects. © 2020 Society of Chemical Industry Abstract : Insects encompass the largest number of migratory animals, but their small body size impedes our understanding of insect migration in the wild, particularly the source populations of immigrants and distance of movement. This study unraveled migration trajectories of a pest insect, the diamondback moth, by deciphering connectivity among potential source and recipient populations from genomic variations. © 2020 Society of Chemical Industry